Effect of a 12-week eccentric and isometric training in achilles tendinopathy on the gastrocnemius muscle: An ultrasound shear wave elastography study - Gatz, Matthias; Tingart, M.; Michalik, R.; Migliorini, F.; Dirrichs, T.; Kuhl, C.; Quack, V.; Betsch, Marcel (Muscle, Ligaments and Tendons Journal, 2020)
Background. Eccentric exercises (EE) and isometric exercises (ISO) are standard treatment options for Achilles tendinopathy, but still their exact effect remains uncertain. Shear Wave Elas-tography (SWE) was used to examine the influence of these exercises on the elastic properties of Mm. gastrocnemii medialis and lateralis in a 12-week training program. Methods. Prospective study with patients suffering from Achilles tendinopathy, which were randomised into 2 groups and conducted exercises for 12 weeks on the symptomatic limb: EE (n=15, 9 male, 55a ± 6.5) and EE+ISO (n=15, 10 male, 47a ± 16.1). Shear Wave Elastography of the gastrocnemius medialis (MG) and lateralis (ML) was made before exercises (T0), after 4 (T1) and 12 weeks (T2) using an established protocol. Results. Muscles of asymptomatic and symptomatic legs did not differ at baseline neither for EE (p=0.139) nor for EE+ISO (p=0.778). SWE values of MG and ML of symptomatic limbs showed no significant alterations neither for EE and EE+ISO nor for the whole population (p=0.567-0.746) without any difference between EE vs. EE+ISO for the whole study period (T0: p=0.247, T1: p=0.990, T2: p=0.516). Contrary, MG and ML of the asymptomatic untrained limb showed increased SWE values over the course for the EE-group (p=0.041) and the whole population (p=0.003) with a significant difference of the symptomatic and asymptomatic limb at T2 for the EE group (p=0.01) and the whole population (p=0.03). MG and ML of asymptomatic limbs differed significantly between EE vs. EE+ISO at T2 (p=0.03), showing higher SWE values for EE. Conclusions. Using Shear Wave Elastography there was no measurable effect neither for EE nor for EE+ISO on MG and ML of symptomatic limbs over a 12-week intervention period. Contrary, in the asymptomatic untrained limb elastic properties increased in the EE group which might be based on the cross-education effect.
CRIS-Team Scopus Importer:2022-07-20
Keywords: Achilles tendinopathy; Eccentric exercises; Isometric exercises; Muscle; Shear wave elastography